A Model for Mission Dentistry in a Developing Country - Tepe, Jan Hexamer; Tepe, Lawrence J. (Frontiers in Public Health, 2017)
Each year many dentists embark on mission trips to foreign countries. This article shares what one group learned in their journey over the course of 17 years to bring oral health to a rural community in Honduras. The group began by delivering acute dental care, but soon realized that this treatment would never change the status of oral health in the community. Year by year they learned what worked and what didn’t. A school based dental prevention program was initiated using proven preventive techniques to demonstrate to the community that prevention of oral disease was possible. As of 2015, the school based program had grown to over ten schools and more than 1,000 children had benefitted from this program. Children in the program received all necessary treatment for the prevention and treatment of dental caries. As importantly, they and their families learned to understand how to be responsible for their own dental needs. In conclusion, it is possible to effect long term change in a developing country by focusing on prevention of oral problems rather than focusing on the extraction hopeless teeth. The good intentions, time, and financial resources of volunteers can be put to best use by first learning about the needs and wants of a particular community. The authors recommend that volunteers partner with local health care providers and research what other organizations are currently doing in their country of interest.